2004
DOI: 10.1191/0309133304pp403ra
|View full text |Cite
|
Sign up to set email alerts
|

Artificial drainage of peatlands: hydrological and hydrochemical process and wetland restoration

Abstract: Peatlands have been subject to artificial drainage for centuries. This drainage has been in response to agricultural demand, forestry, horticultural and energy properties of peat and alleviation of flood risk. However, the are several environmental problems associated with drainage of peatlands. This paper describes the nature of these problems and examines the evidence for changes in hydrological and hydrochemical processes associated with these changes. Traditional black-box water balance approaches demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
389
3
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 453 publications
(399 citation statements)
references
References 69 publications
3
389
3
4
Order By: Relevance
“…The effects of drainage on DOC have been controversial for a long time (see review by Holden et al 2004). Recent studies have found increased leaching and pore water concentrations of DOC soon after excavation of ditches (Wallage et al 2006; and drainage has been suggested to increase leaching of DOC to downstream watercourses (Huotari et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of drainage on DOC have been controversial for a long time (see review by Holden et al 2004). Recent studies have found increased leaching and pore water concentrations of DOC soon after excavation of ditches (Wallage et al 2006; and drainage has been suggested to increase leaching of DOC to downstream watercourses (Huotari et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…pH and concentrations of several chemical elements increase in the pore and outflow water shortly after drainage , Moore et al 2013. In contrast, long-term changes of pore water chemistry after drainage are not well understood (Holden et al 2004). Drainage has also marked effects on peatland ecosystem structures like plant community composition , Mälson et al 2008).…”
Section: Degradation and Restoration Of Peatland Ecosystemsmentioning
confidence: 99%
See 3 more Smart Citations